Optimal location selection for digital television signal booster towers in poorly covered areas: application of the EDIS multi-criteria decision-making method - Mehdi Soltanifar (تصمیم گیری و تحقیق در عملیات)
Purpose: The purpose of this paper is to address the significant challenge of optimizing the placement of digital television signal booster towers to ensure quality coverage and equitable access to high-quality media services in today’s digital landscape. This paper introduces a novel multi-criteria decision-making method, named Evaluation based on Distance from Ideal Solution (EDIS), inspired by the EDAS method, aimed at enhancing decision-making processes in this context.Methodology: The EDIS method is utilized for the optimal placement of digital television signal booster towers. The method considers various cost and benefit criteria, including annual maintenance cost, tower price, signal sensitivity and boosting power, unmet quality standards, operator complexity level, and interference resistance, to determine the most suitable locations for tower placement.Findings: The application of the EDIS method to a real-world case study demonstrates significant improvements in decision-making accuracy and efficiency over existing methods, offering enhanced support for optimal decision-making in the placement of digital television signal booster towers.Originality/Value: The proposed EDIS method presents a novel multi-criteria decision-making tool that combines innovative features with advanced optimization capabilities. It contributes significant scientific value to the field by providing an effective solution for optimizing the location of digital television signal booster towers, thereby enhancing decision-making processes in this domain.